Synthesis and characterization of Eu3+ doped TiO2 thin films deposited by spray pyrolysis technique for photocatalytic application - S M AL-Shomar (Materials Research Express, 2021)
In this study, nanocrystalline TiO _2 : Eu ^3+ thin films are successfully formed by spray pyrolysis technique deposited on glass substrate. Structure, optical, electrical, surface morphology, and photocatalytic degradation of Methylene blue have been examined. The XRD analysis illustrate the tetragonal crystal structure of films with anatase phase and reduces crystallite size linearly with increasing Eu ^3+ concentration. The optical properties of the films are analyzed using transmittance and reflectance spectra, which are measured using UV–vis-NIR double-beam spectrophotometer. Optical properties such as refractive index (n), extinction coefficient (k), optical conductivity (σ) and Urbach energy (E _u ) have been calculated as a function of Eu ^3+ concentration. Film thickness were evaluated using the refractive index dependence on wavelength. The films thickness were determined as 97.13, 122.62, 123.24, 117.14 and 128.25 nm, respectively, for Eu doped TiO _2 at 0,4, 6, 8 and 10 wt % doping concentration. The band gap values raised from 3.29 to 3.42 eV with increasing the Eu ^3+ dopant concentration. The highest electrical conductivity was found to be 3.01 × 10 ^−2 (Ω·cm) ^−1 at high doping level with 10 wt% Eu ^3+ . Scanning electron microscopy (SEM) analysis indicated consistent allocation of irregular and spherical shaped grains covering the substrate surface. The average grain size in range of 82.5—51.1 nm is observed and films show porous nature. The photocatalytic effect of TiO _2 : Eu ^3+ thin films is predicted from the degradation of methylene blue (MB) at room temperature under UV light irradiation. An enhancement in photocatalytic degradation observed by increasing the amount of Eu ^3+ due to increase in the (electron-hole) pair production and increase of film thickness. These results make TiO _2 : Eu ^3+ thin films as attractive candidate for photovoltaic cells and other optoelectronic device applications.